UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA KARTU ALFABET BERGAMBAR PADA ANAK USIA DINI 4-5 TAHUN DI TK RUMAH BUNDA ISLAMIC PRESCHOOL KARAWANG - Fauziah, Eva; Darmiyanti, Astuti; Putri, Feronica Eka (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The aim of this classroom action research is to help children aged 4 to 5 years in group A Kindergarten Rumah Bunda Islamic Preschool Karawang improve their initial reading skills using illustrated alphabet cards. This research is PTK, which means classroom action research. This research method involves four stages of planning, action, implementation, and reflection. The focus of this research was 11 children in group A Kindergarten Rumah Bunda Islamic Preschool Karawang. Data is collected through observation and documentation. As many as 75% of the 11 children showed an increase in initial reading ability, which is an indicator of success in early childhood. This research was conducted in two cycles; cycle I lasted for 6 meetings, and cycle II lasted for 4 meetings. The results of the study showed an increase in early reading abilities in children aged 4 to 5 years using picture alphabet cards as media. Children at the Rumah Bunda Islamic Preschool Karawang Kindergarten succeeded in improving their reading skills through learning games using this media. The average percentage of reading ability before the action was 19.4%, increased to 89.3% in cycle I, and reached 116.8% in cycle II”.